2007
DOI: 10.1111/j.1399-3054.2007.00903.x
|View full text |Cite
|
Sign up to set email alerts
|

Two defined alleles of the LRR receptor kinase GmNARK in supernodulating soybean govern differing autoregulation of mycorrhization

Abstract: Plants regulate the extent of nodulation and root colonization by arbuscular mycorrhizal fungi (AMF), a phenomenon named autoregulation of symbiosis. We tested AMF colonization in split roots of various soybean genotypes [Glycine max (L.) Merr. cv. Bragg, Enrei, Harosoy and Williams], where precolonization of one side of the split‐root system by the AMF Glomus mosseae resulted in reduced mycorrhization of the other. AMF precolonization failed to control secondary mycorrhization in the supernodulating Bragg non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
1
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 55 publications
1
33
1
1
Order By: Relevance
“…During their evolution, legumes developed nodulation and mycorrhization systems to attain mutual symbiosis with rhizobia and mycorrhizae (Harrison, 2005;Stacey et al, 2006). Although plants are known to control the degrees of nodulation and mycorrhization of roots by rhizobia and mycorrhizae, respectively, through autoregulation systems (Carroll et al, 1985;Meixner et al, 2007), the effects of the autoregulation systems on the other plant-associated microorganisms in the phytosphere remain unclear (Parniske, 2000). Recent studies have shown that the wild-type and symbiosisdefective mutants of legumes such as Medicago truncatula and Glycine max have different microbial community structures, and certain microbes associate preferentially with nodulated or mycorrhizal root systems (Offre et al, 2007;Ikeda et al, 2008a).…”
Section: Introductionmentioning
confidence: 99%
“…During their evolution, legumes developed nodulation and mycorrhization systems to attain mutual symbiosis with rhizobia and mycorrhizae (Harrison, 2005;Stacey et al, 2006). Although plants are known to control the degrees of nodulation and mycorrhization of roots by rhizobia and mycorrhizae, respectively, through autoregulation systems (Carroll et al, 1985;Meixner et al, 2007), the effects of the autoregulation systems on the other plant-associated microorganisms in the phytosphere remain unclear (Parniske, 2000). Recent studies have shown that the wild-type and symbiosisdefective mutants of legumes such as Medicago truncatula and Glycine max have different microbial community structures, and certain microbes associate preferentially with nodulated or mycorrhizal root systems (Offre et al, 2007;Ikeda et al, 2008a).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the signals involved in both nodulation and mycorrhization overlap in a common signaling pathway, leading to successful symbioses (31,32). Leguminous plants are also known to regulate the degree of nodulation and mycorrhization of roots by rhizobia and mycorrhizae, respectively (3,28). This autoregulatory mechanism occurs through long-distance signaling between the shoot and root (30).…”
mentioning
confidence: 99%
“…AB213415 is a root-associated fungal sequence isolated from the rhizosphere of chrysanthemum. Uncultured basidiomycetes TP1 and TPC2 (accession numbers AY382817 and AY382818) were reported to be orchid mycorrhizae by McCormick et al (16 Fig. 3, the sequences of clones F1 and F4 are more closely related to known species of Auricularia and Exidia/Exidiopsis.…”
Section: Discussionmentioning
confidence: 99%
“…Plants deficient in autoregulation of nodulation develop hypernodulated roots. In the case of soybean [Glycine max (L.) Merril], hypernodulated mutants differ in their ability to autoregulate root colonization by arbuscular mycorrhizal fungi (16). However, the degree to which plants use similar or identical systems, such as a common signaling pathway and autoregulation, for interactions with other microorganisms remains unclear (23).…”
mentioning
confidence: 99%
See 1 more Smart Citation